2023
DOI: 10.1186/s13287-023-03357-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficacy of human dental pulp stem cells and scaffold combination for bone regeneration in animal models: a systematic review and meta-analysis

Abstract: Introduction Human adult dental pulp stem cells (hDPSC) and stem cells from human exfoliated deciduous teeth (SHED) hold promise in bone regeneration for their easy accessibility, high proliferation rate, self-renewal and osteogenic differentiation capacity. Various organic and inorganic scaffold materials were pre-seeded with human dental pulp stem cells in animals, with promising outcomes in new bone formation. Nevertheless, the clinical trial for bone regeneration using dental pulp stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Dental MSCs (DMSCs) have been found in various dental tissues; moreover, DMSCs have gained growing interest from the scientific community because of their easy accessibility, and thanks to their high strategic plasticity both in dental tissues repair and in regenerating several types of human tissues, including bone, cartilage, muscle, and neural tissue. Despite oral tissues not being the most used niches of MSCs, we should carefully rethink the role of DMSCs in tissue regeneration, as their use may lead to a significant advance of knowledge in regenerative dentistry, impacting on the future treatments of various systemic diseases (Namjoynik et al, 2023;Tatullo et al, 2023).This Research Topic has investigated a wide range of Research Topic, confirming the valuable potentialities of DMSCs in tissue regeneration. Several approaches have been proposed to optimize and enhance the regenerative potential of MSC, such as the use of media conditioned with different growth factors, or cytokines and bioactive molecules (Liu et al, 2022;Ueda et al, 2022).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Dental MSCs (DMSCs) have been found in various dental tissues; moreover, DMSCs have gained growing interest from the scientific community because of their easy accessibility, and thanks to their high strategic plasticity both in dental tissues repair and in regenerating several types of human tissues, including bone, cartilage, muscle, and neural tissue. Despite oral tissues not being the most used niches of MSCs, we should carefully rethink the role of DMSCs in tissue regeneration, as their use may lead to a significant advance of knowledge in regenerative dentistry, impacting on the future treatments of various systemic diseases (Namjoynik et al, 2023;Tatullo et al, 2023).This Research Topic has investigated a wide range of Research Topic, confirming the valuable potentialities of DMSCs in tissue regeneration. Several approaches have been proposed to optimize and enhance the regenerative potential of MSC, such as the use of media conditioned with different growth factors, or cytokines and bioactive molecules (Liu et al, 2022;Ueda et al, 2022).…”
mentioning
confidence: 68%
“…Dental MSCs (DMSCs) have been found in various dental tissues; moreover, DMSCs have gained growing interest from the scientific community because of their easy accessibility, and thanks to their high strategic plasticity both in dental tissues repair and in regenerating several types of human tissues, including bone, cartilage, muscle, and neural tissue. Despite oral tissues not being the most used niches of MSCs, we should carefully rethink the role of DMSCs in tissue regeneration, as their use may lead to a significant advance of knowledge in regenerative dentistry, impacting on the future treatments of various systemic diseases (Namjoynik et al, 2023;Tatullo et al, 2023).…”
mentioning
confidence: 99%
“…In animal and pre‐clinical studies, PDLMSCs (Bright et al, 2015; Tassi et al, 2017) and DPSCs (Leyendecker Junior et al, 2018; Namjoynik et al, 2023) have been extensively investigated. The two cell types were also found to show comparable osteogenic capability as BMSCs (Kadkhoda et al, 2024; Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that hDPSCs for BTE are abundant, easily accessible, can be harvested with minimal invasiveness, and grow efficiently in culture [ 42 , 43 ]. Accumulating evidence indicates that the microenvironment influences the fate of hDPSCs by regulating signalling pathways and genes associated with differentiation [ 18 , 43 ]. The development of functional hydrogel scaffolds that mimic ECM is a promising strategy for BTE.…”
Section: Discussionmentioning
confidence: 99%